2015
DOI: 10.1007/s00264-015-3022-1
|View full text |Cite
|
Sign up to set email alerts
|

A critical analysis of radiographic factors in patients who develop dislocation after elective primary total hip arthroplasty

Abstract: In this study, 90 % of patients who developed a dislocation had properly positioned acetabular components. In addition, the vast majority of patients in the study group had adequate restoration of limb length and offset. The results of our study may be useful for the orthopedic surgeons who discuss instability following THA surgery, particularly in patients with radiographically sound reconstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
0
19
1
Order By: Relevance
“…2015, Opperer et al. 2016). The other articles listed in Table 8 did not verify the differences between dislocators and non-dislocators in the Lewinnek safe zone with statistical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…2015, Opperer et al. 2016). The other articles listed in Table 8 did not verify the differences between dislocators and non-dislocators in the Lewinnek safe zone with statistical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…24 Opperer et al reported that dislocations occurred when acetabular components were well positioned in 88.7% of their cases. 3 Seagrave et al recently performed a systematic review of 28 published articles on prosthetic joint dislocation and were unable to successfully identify a safe zone for acetabular component position based on the literature. 25 The results of our study suggest that dislocation risk is increased for hips reconstructed with increased acetabular inclination or reduced acetabular anteversion < 15 degrees.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of dislocation following primary THA has been reported between 2 and 5%. [1][2][3][4][5] The risk of THA dislocation may be influenced by patient sex, diagnosis, surgical approach, implant selection, component position, and soft tissue balance. [6][7][8][9][10][11][12] Improvements in femoral stem design that allow more consistent femoral offset restoration, improvements in polyethylene materials that enable use of larger femoral head sizes, and the inclusion of capsular closure with posterior hip approaches may contribute to lower early dislocation risk.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17 studies reported on mean anteversion between the control groups and the groups with dislocation. 18,19,24,[27][28][29][30]32,[34][35][36]38,41,42 3 studies (from Ezquerra-Herrando et al, 25 Opperer et al 37 and Sadhu et al 39 ), showed a statistically significant difference between the control group and the group with dislocations, (mean anteversion of 14.19 vs. 11.54 [p = 0.043], 16.62 vs. 17.73 [p = 0.06], 17.6 vs. 20.5 [p = 0.04] respectively). 4 of the 28 included studies differentiated between anterior and posterior dislocations (Table 2).…”
Section: Acetabular Cup Orientationmentioning
confidence: 99%